Long-Term Storage of Seeds from Plant Gene Pool Samples in the National Depository - Chernobai, Yuliia; Riabchun, Viktor; Kuzmyshyna, Nataliia; Shyianova, Tetyana; Bohuslavskyi, Roman (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):296